Perwujudan Bentuk Arsitektur Berbasis Aktivitas Sehari-hari: Studi Kasus: Pendekatan Maya Lin dan Eko Prawoto - Johannes Adiyanto (ATRIUM: Jurnal Arsitektur, 2021)
Title: Architectural Forming in Daily Activities (Case Study: Maya Lin and Eko Prawoto Approach)   Form is the based architecture. The idea of architecture can come true in the form. Architecture can become a container of human activities because form and space. This paper focusses on architectural form. The main question in this paper is how the architect creating their form’s based on their daily activities? This paper used qualitative phenomenology method to phenomenology hermeneutics approach. This method place the daily activities of responding. The cases are Maya Lin’s Vietnam Veteran Memorial and House of Eko Prawoto’s. Their cases were interpreted with Mangunwijaya thinking with written at Ragawidya. This paper shows that architectural form is a manifestation of the contemplation proses and from daily activities. The forming of architectural form is also a process of expression of the deposition of experiencing in the past time which carried out continuously. The result of forming is not an astonishing form, but familiar with everyday life.